Neotypification of the name Rosa agrestis (Rosaceae) - Roma-Marzio, Francesco; D’antraccoli, Marco; Astuti, Giovanni; Maccioni, Simonetta; Peruzzi, Lorenzo (Phytotaxa, 2016)
Gaetano Savi (1769–1844) worked at the University of Pisa and was a prominent figure among Italian botanists of the XIX century. He published about 75 scientific papers, primarily devoted to floristic researches and taxonomical investigations. During his career, he described 89 taxa of vascular plants (6 genera and 83 species). In the frame of a typification project devoted to the names described by Gaetano Savi (D’Antraccoli et al. 2015), we found that up to now only 8 names (ca. 9%) have been typified (Zohary & Heller 1984, Baldini & Jarvis 1991, Garbari & Cecchi 2000, Selvi & Cecchi 2009, O’Leary 2010, Amadei et al. 2013, 2015, Alonso et al. 2016). One of the names still lacking a typification is Rosa agrestis Savi (1798: 475), a species occurring in the most part of Europe, Russia, Anatolia and in the North-Western part of Africa (Silvestre & Montserrat 1998). Rosa agrestis belongs to R. sect. Caninae Candolle (1818: 3) emend. Christ (1873: 36), the most numerous and taxonomically complex section in Europe (Bruneau et al. 2007, De Cock et al. 2008). However, since its description, R. agrestis was recognized as a distinct species by most authors (e.g. Kláštersky 1968, Pignatti 1982, Lattanzi & Tilia 2002, Tison & de Foucault 2014).